ALS/FTD mutations in UBQLN2 are linked to mitochondrial dysfunction through loss-of-function in mitochondrial protein import. Issue 13 (22nd April 2021) - Lin, Brian C; Phung, Trong H; Higgins, Nicole R; Greenslade, Jessie E; Prado, Miguel A; Finley, Daniel; Karbowski, Mariusz; Polster, Brian M; Monteiro, Mervyn J
Abstract: UBQLN2 mutations cause amyotrophic lateral sclerosis (ALS) with frontotemporal dementia (FTD), but the pathogenic mechanisms by which they cause disease remain unclear. Proteomic profiling identified 'mitochondrial proteins' as comprising the largest category of protein changes in the spinal cord (SC) of the P497S UBQLN2 mouse model of ALS/FTD. Immunoblots confirmed P497S animals have global changes in proteins predictive of a severe decline in mitochondrial health, including oxidative phosphorylation (OXPHOS), mitochondrial protein import and network dynamics. Functional studies confirmed mitochondria purified from the SC of P497S animals have age-dependent decline in nearly all steps of OXPHOS. Mitochondria cristae deformities were evident in spinal motor neurons of aged P497S animals. Knockout (KO) of UBQLN2 in HeLa cells resulted in changes in mitochondrial proteins and OXPHOS activity similar to those seen in the SC. KO of UBQLN2 also compromised targeting and processing of the mitochondrial import factor, TIMM44, resulting in accumulation in abnormal foci. The functional OXPHOS deficits and TIMM44-targeting defects were rescued by reexpression of WT UBQLN2 but not by ALS/FTD mutant UBQLN2 proteins. In vitro binding assays revealed ALS/FTD mutant UBQLN2 proteins bind weaker with TIMM44 than WT UBQLN2 protein, suggesting that the loss of UBQLN2 binding may underlie the import and/or delivery defect of TIMM44 to mitochondria. Our studies indicate a potential key pathogenic disturbance in mitochondrial health caused by UBQLN2 mutations.